Closed Circuit Television in Public Places - Clancey, Garner (2007)
Garner Clancey (Adjunct Lecturer, Sydney Institute of Criminology) has developed a number of crime prevention fact sheets. These fact sheets provide an overview of key crime prevention tenets and cover various topics and issues. They have been designed to assist practitioners in their work and to provide a link to relevant crime prevention research. This fact sheet considers a number of issues that should be considered in great detail before installing closed circuit television (CCTV) cameras in public areas as a crime prevention initiative